Ultrasound Demonstration of a Benign Gastric Ulcer with Gastric Outlet Obstruction - PL Pattee; HH Tao; R Bhargava; A Al-Alwadhi (Canadian Journal of Gastroenterology)
A benign antral gastric ulcer in an adult causing gastric outlet obstruction was demonstrated by ultrasonography. The extent and benign nature of the ulcer was suggested by ultrasound before gastric surgery was performed. Features implying a benign gastric ulcer were: observation of peristaltic waves through the underlying muscular layer, homogenicity of the ulcer crater and characteristic mound or volcano-like appearance of the heaped-up folds of mucosa. The differential diagnosis and the role of ultrasound in the diagnosis of gastric ulcers are discussed.